Multi-element graded composite hollow microsphere wave-absorbing agent as well as preparation method and application thereof

By adopting a multivariate graded composite hollow microsphere wave absorber, the cavity structure and the synergistic effect of porous amorphous carbon and carbon nano-angle magnetic metal composite particles are solved, and the existing carbon-based magnetic composite materials are achieved with high efficiency electromagnetic wave absorption effect.

CN119592302APending Publication Date: 2025-03-11AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411791044.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing carbon-based magnetic composite materials have poor wave absorption performance and cannot maximize the synergistic effect between carbon and magnetic components.

Method used

Multi-variable graded composite hollow microsphere wave absorber is used, which consists of a hollow core and a composite spherical shell. The hollow core is an air cavity. The composite spherical shell consists of porous amorphous carbon and carbon nanoangular magnetic metal composite particles, and is prepared by atomization and drying and heat treatment.

Benefits of technology

Through multiple interface effects and multiple loss mechanisms, the synergistic effect of magnetic-dielectric-conductive three is achieved, significantly enhancing electromagnetic wave loss and absorption capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175317720000111
    Figure BDA0005175317720000111
  • Figure BDA0005175317720000121
    Figure BDA0005175317720000121
Patent Text Reader

Abstract

The invention provides a multi-element graded composite hollow microsphere wave-absorbing agent as well as a preparation method and application thereof. The multi-element graded composite hollow microsphere is composed of a hollow core and a composite spherical shell, wherein the hollow inner core is an air cavity, and the composite spherical shell is composed of porous amorphous carbon serving as a continuous phase and carbon nanohorn and magnetic metal composite particles serving as a dispersed phase. According to the scheme, the hollow core of the multi-element graded composite hollow microsphere is the air cavity, the density is low, and electromagnetic waves can be induced to enter the hollow cavity for multi-reflection; the composite spherical shell is composed of porous amorphous carbon serving as a continuous phase and carbon nanohorn-magnetic metal composite particles serving as a dispersed phase, tiny pores in the amorphous carbon can provide more interface polarization, and meanwhile, the amorphous carbon and the carbon nanohorn-magnetic metal composite particles can form a multi-element heterogeneous interface on the surface of the composite spherical shell; through a multi-interface effect and a multi-loss mechanism among the carbon nanohorn, the magnetic metal and the amorphous carbon, the electromagnetic wave loss is effectively enhanced and increased, and the electromagnetic wave absorption capability is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microwave absorbing agent preparation, and in particular to a multi-element hierarchical composite hollow microsphere absorbing agent and a preparation method and application thereof. Background Art

[0002] With the rapid development of wireless communications and the electronics industry, more and more electromagnetic radiation and electromagnetic interference are generated, which seriously pollute the environment and affect the normal operation of equipment and human health. New carbon-based magnetic composite absorbing materials have become the mainstream of research on electromagnetic wave absorbing materials because of their light weight and high performance.

[0003] New carbon-based magnetic composite absorbing materials can achieve the coordinated effect of multiple loss mechanisms such as conductive loss, multiple scattering, interface polarization and magnetic loss through strategies such as microstructure design, multi-component composite and nano-level construction. Its comprehensive absorbing mechanism is conducive to improving the impedance matching level and weakening the influence of eddy current effect, thereby achieving high strength, wide bandwidth, thin thickness and good stability. However, many carbon-based magnetic composite materials currently have single components and structures, which cannot maximize the synergistic effect between carbon and magnetic components, resulting in poor absorbing performance of carbon-based magnetic composite materials.

[0004] Based on this, there is an urgent need to provide a multi-element hierarchical composite hollow microsphere absorber and its preparation method and application. Summary of the invention

[0005] The embodiment of the present invention provides a multi-element hierarchical composite hollow microsphere absorber and a preparation method and application thereof, which can solve the problem of poor absorption performance of traditional carbon-based magnetic composite materials.

[0006] In a first aspect, the present invention provides a multi-element hierarchical composite hollow microsphere absorber, wherein the multi-element hierarchical composite hollow microsphere is composed of a hollow core and a composite spherical shell; wherein the hollow core is an air cavity, and the composite spherical shell is composed of porous amorphous carbon as a continuous phase and carbon nanohorn@magnetic metal composite particles as a dispersed phase.

[0007] Preferably, the density of the multi-element graded composite hollow microspheres is 0.5-3.0 g / cm 3 , diameter is 5-100μm, and the thickness of the composite spherical shell is 0.1-20μm.

[0008] Preferably, the porous amorphous carbon is obtained by carbonizing a water-soluble organic carbon source; wherein the organic carbon source is at least one of glucose, fructose, sucrose, citric acid or dopamine; and the magnetic metal is at least one of metallic iron, metallic cobalt or metallic nickel.

[0009] In a second aspect, the present invention provides a multi-element hierarchical composite hollow microsphere absorber as described in any one of the first aspects above, wherein the preparation method comprises the following steps:

[0010] (1) pretreating the carbon nanohorn particles to obtain pretreated carbon nanohorn particles;

[0011] (2) placing the pretreated carbon nanohorn particles in an assembly reaction solution to self-assemble with a magnetic metal to obtain carbon nanohorn@magnetic metal composite particles;

[0012] (3) mixing the carbon nanohorn@magnetic metal composite particles with an organic carbon source and water, and then atomizing and drying the mixed slurry using an atomizing dryer to obtain a composite hollow microsphere precursor;

[0013] (4) heat-treating the composite hollow microsphere precursor to obtain the multi-element graded composite hollow microsphere absorber.

[0014] Preferably, in step (1), the pretreatment comprises the steps of sequentially performing acid washing and activation treatment on the carbon nanohorns;

[0015] During the pickling process, the mass volume ratio of the carbon nanohorn particles to the acid solution is 1:(2-6) g / mL, and the acid solution is at least one of acetic acid, hydrochloric acid, sulfuric acid or nitric acid;

[0016] Preferably, the concentration of the acid solution is 0.5-1.0 mol / L, and the pickling time is 30-120 min.

[0017] Preferably, in step (1), during the activation treatment, the mass volume ratio of the carbon nanohorn particles to the activated aqueous solution is 1:(5-10) g / mL, and the solute in the activated aqueous solution is at least one of tin ions, palladium ions, silver ions, gold ions or platinum ions.

[0018] Preferably, the concentration of the activated aqueous solution is 0.05-0.15 mol / L, and the activation treatment time is 5-10 min.

[0019] Preferably, in step (2), the assembly reaction solution comprises a metal salt, a metal complexing agent, a reducing agent and a pH adjusting agent; wherein the metal salt is at least one of an iron salt, a nickel salt or a cobalt salt, the metal complexing agent is at least one of ammonium sulfate, potassium sodium tartrate or ethylenediaminetetraacetic acid, the reducing agent is at least one of sodium hypophosphite, hydrazine hydrate, formaldehyde or sodium borohydride, and the pH adjusting agent is at least one of sodium hydroxide or potassium hydroxide.

[0020] Preferably, in the assembly reaction solution, the concentration of the metal salt is 10-20 g / L, the concentration of the metal complexing agent is 30-50 g / L, the concentration of the reducing agent is 50-80 g / L, and the pH of the assembly reaction solution is 9-11.

[0021] More preferably, the mass volume ratio of the carbon nanohorn particles to the assembly reaction solution is 1: (20-30) g / mL.

[0022] Preferably, in step (3), the mass ratio of carbon nanohorn@magnetic metal composite particles, organic carbon source and water is (50-250):(25-180):(300-500).

[0023] Preferably, in step (3), when atomization drying is performed, the injection speed of the mixed slurry is 10-25 mL / min, the inlet temperature of the atomization dryer is 200-350°C, and the outlet temperature is 110-130°C.

[0024] Preferably, in step (4), the heat treatment temperature is 400-700° C. and the time is 1-10 h.

[0025] In a third aspect, the present invention provides an application of the multi-element hierarchical composite hollow microsphere absorber described in any one of the first aspects or the multi-element hierarchical composite hollow microsphere absorber prepared by the preparation method described in any one of the second aspects in microwave absorption and catalytic degradation of wastewater.

[0026] Compared with the prior art, the present invention has at least the following beneficial effects:

[0027] The multi-element hierarchical composite hollow microspheres in the present invention are composed of a hollow core and a composite spherical shell. The inner shell of the composite hollow microspheres is an air cavity. The density of the hollow core is relatively low, which can reduce the density of the composite hollow microsphere absorber and induce electromagnetic waves to enter the hollow cavity for multiple reflections. The carbon nanohorns coated with magnetic metal particles are used as the smallest unit to form carbon nanohorn@magnetic metal composite particles. The dispersion of carbon nanohorns and metals can be increased by the supporting and dispersing effect of the continuous phase amorphous carbon. At the same time, the tiny pores in the amorphous carbon can provide more interface polarization. Combined with the certain permeability of carbon to electromagnetic waves, the porous amorphous carbon as a defect can form a multi-element heterogeneous interface with the carbon nanohorn@magnetic metal composite particles on the surface of the composite spherical shell. Through the multiple interface effects and multiple loss mechanisms between the carbon nanohorns, the magnetic metal and the amorphous carbon, the synergistic effect of magnetism, dielectricity and conductivity is satisfied, thereby effectively enhancing the increase of electromagnetic wave loss and enhancing the electromagnetic wave absorption capacity. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] An embodiment of the present invention provides a multi-element hierarchical composite hollow microsphere absorber, wherein the multi-element hierarchical composite hollow microsphere is composed of a hollow core and a composite spherical shell; wherein the hollow core is an air cavity, and the composite spherical shell is composed of porous amorphous carbon as a continuous phase and carbon nanohorn@magnetic metal composite particles as a dispersed phase.

[0030] The multi-level hierarchical composite hollow microspheres in the embodiment of the present invention are composed of a hollow core and a composite spherical shell. The inner shell of the composite hollow microsphere is an air cavity. The density of the hollow core is relatively low, which can reduce the density of the composite hollow microsphere absorber and induce electromagnetic waves to enter the hollow cavity for multiple reflections. The carbon nanohorns coated with magnetic metal particles are used as the smallest unit to form carbon nanohorn@magnetic metal composite particles. The dispersion of carbon nanohorns and metals can be increased by the supporting and dispersing effect of the continuous phase amorphous carbon. At the same time, the tiny pores in the amorphous carbon can provide more interface polarization, combined with the certain permeability of carbon to electromagnetic waves. At the same time, the porous amorphous carbon is used as a defect, and can form a multi-level heterogeneous interface with the carbon nanohorn@magnetic metal composite particles on the surface of the composite spherical shell. Through the multiple interface effects and multiple loss mechanisms between carbon nanohorns, magnetic metals and amorphous carbon, the synergistic effect of magnetism, dielectricity and conductivity is satisfied, thereby effectively enhancing the increase of electromagnetic wave loss and enhancing the electromagnetic wave absorption capacity.

[0031] According to some preferred embodiments, the density of the multi-level graded composite hollow microspheres is 0.5-3.0 g / cm 3 (For example, it can be 0.5g / cm 3 , 0.8g / cm 3 , 1.0g / cm 3 , 1.5g / cm 3 , 2g / cm 3 , 2.5g / cm 3 or 3g / cm 3 ), a diameter of 5-100μm (for example, it can be 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm or 100μm), preferably 10-70μm, and the thickness of the composite spherical shell is 0.1-20μm (for example, it can be 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 15μm or 20μm).

[0032] In the embodiment of the present invention, the size, density, etc. of the multi-component graded composite hollow microspheres are controlled within the above ranges by reasonably controlling the proportion of the raw materials of each component and the process parameters during the preparation process. This is not only conducive to ensuring the lightness of the composite hollow microspheres, but also conducive to forming composite hollow microspheres with a multi-component synergistic loss mechanism, thereby achieving high-intensity and broadband electromagnetic wave absorption.

[0033] According to some preferred embodiments, the porous amorphous carbon is obtained by carbonizing a water-soluble organic carbon source; wherein the organic carbon source is at least one of glucose, fructose, sucrose, citric acid or dopamine; and the magnetic metal is at least one of metallic iron, metallic cobalt or metallic nickel.

[0034] In the embodiment of the present invention, the porous amorphous carbon is used as a continuous phase in the composite hollow microspheres, which is mainly obtained by carbonizing a water-soluble organic carbon source at high temperature. The carbonized porous amorphous carbon has pores with a pore diameter of 10-60nm. At the same time, it should be noted that the size of the carbon nanohorns in the embodiment of the present invention is 1-50nm, which is conducive to the composite molding of the microspheres in the composite.

[0035] The present invention also provides a method for preparing the multi-element hierarchical composite hollow microsphere absorber described in any one of the above items, the preparation method comprising the following steps:

[0036] (1) pre-treating the carbon nanohorn particles in sequence to obtain pre-treated carbon nanohorn particles;

[0037] (2) placing the pretreated carbon nanohorn particles in an assembly reaction solution to self-assemble with a magnetic metal to obtain carbon nanohorn@magnetic metal composite particles;

[0038] (3) mixing the carbon nanohorn@magnetic metal composite particles with an organic carbon source and water, and then atomizing and drying the mixed slurry using an atomizing dryer to obtain a composite hollow microsphere precursor;

[0039] (4) heat-treating the composite hollow microsphere precursor to obtain the multi-element graded composite hollow microsphere absorber.

[0040] In the embodiment of the present invention, the above-mentioned preparation method is conducive to preparing composite hollow microspheres with low density and suitable size, and can realize the graded design of the structure and performance of the composite hollow microspheres by regulating the process parameters and the raw material ratio. At the same time, the preparation method has the advantage of simple process, which is conducive to the efficient preparation of large quantities of composite hollow microspheres, and thus is conducive to the batch preparation and application development of lightweight absorbers.

[0041] During the preparation process, the density of the composite hollow microspheres can be reduced by adjusting the size of the air cavity in the hollow core, thereby ensuring the lightness of the absorber; taking carbon nanohorns as the smallest unit, carbon nanohorns can cover magnetic metal particles to form carbon-based hollow composite microspheres, and at the same time, porous amorphous carbon is introduced as a defect, so that a multi-heterogeneous interface is formed on the surface of the composite spherical shell. Through the multiple interface effects and multiple loss mechanisms between carbon nanohorns, magnetic metals and amorphous carbon, the synergistic effect of magnetism, dielectricity and conductivity is met, thereby effectively enhancing the absorption performance of the absorber for electromagnetic waves. At the same time, the composite hollow microspheres have a large micron-level macroscopic size, which can effectively prevent the agglomeration of the composite hollow microsphere particles and facilitate the use of the absorber.

[0042] According to some preferred embodiments, in step (1), the pretreatment comprises the steps of sequentially performing acid washing and activation treatment on the carbon nanohorns; during the acid washing process, the mass volume ratio of the carbon nanohorn particles to the acid solution is 1:(2-6) g / mL (for example, 1:2 g / mL, 1:3 g / mL, 1:4 g / mL, 1:5 g / mL or 1:6 g / mL), and the acid solution is at least one of acetic acid, hydrochloric acid, sulfuric acid or nitric acid; the concentration of the acid solution is 0.5-1.0 mol / L (for example, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1.0 mol / L), and the acid washing time is 30-120 min (for example, 30 min, 45 min, 60 min, 75 min, 90 min or 120 min).

[0043] In the embodiment of the present invention, the carbon nanohorns are first placed in a certain amount of acid solution for mixing and stirring, and then filtered. The concentration of the acid solution and the ratio of the acid solution to the carbon nanohorns during the pickling process are controlled to clean the surface of the carbon nanohorns and enhance the adhesion of the surface of the carbon nanohorns, which is beneficial to the subsequent composite of the carbon nanohorns with magnetic metal particles.

[0044] According to some preferred embodiments, in step (1), during the activation treatment, the mass volume ratio of the carbon nanohorn particles to the activated aqueous solution is 1: (5-10) g / mL (for example, 1: 5 g / mL, 1: 6 g / mL, 1: 7 g / mL, 1: 8 g / mL, 1: 9 g / mL or 1: 10 g / mL), the solute in the activated aqueous solution is at least one of tin ions, palladium ions, silver ions, gold ions or platinum ions; the concentration of the activated aqueous solution is 0.05-0.15 mol / L (for example, 0.05 mol / L, 0.08 mol / L, 0.10 mol / L, 0.12 mol / L or 0.15 mol / L), and the activation treatment time is 5-10 min (for example, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min).

[0045] In the embodiment of the present invention, the acid-washed carbon nanohorn particles are further placed in an activated aqueous solution at a certain temperature (50-60° C.) for stirring reaction, and then filtered, washed and dried, and the agglomerated particles in the system are removed by screening to obtain pre-treated carbon nanohorns. During the activation treatment, the mass ratio of the carbon nanohorn particles to the activated aqueous solution and the concentration of the activated aqueous solution are controlled, so that the adhesion of the carbon nanohorn surface can be further enhanced, which is conducive to the subsequent carbon nanohorn better coating of the magnetic metal particles.

[0046] It should be noted that, in the embodiments of the present invention, when performing activation treatment, palladium chloride, stannous chloride, and silver chloride can be mixed with hydrochloric acid of a certain concentration, and then mixed with a certain amount of water to form an activated aqueous solution.

[0047] According to some preferred embodiments, in step (2), the assembly reaction solution includes a metal salt, a metal complexing agent, a reducing agent and a pH adjusting agent; wherein the metal salt is at least one of an iron salt, a nickel salt or a cobalt salt, the metal complexing agent is at least one of ammonium sulfate, potassium sodium tartrate or ethylenediaminetetraacetic acid, the reducing agent is at least one of sodium hypophosphite, hydrazine hydrate, formaldehyde or sodium borohydride, and the pH adjusting agent is at least one of sodium hydroxide or potassium hydroxide.

[0048] In the assembly reaction solution, in the assembly reaction solution, the concentration of the metal salt is 10-20 g / L (for example, 10 g / L, 12 g / L, 15 g / L, 18 g / L or 20 g / L), the concentration of the metal complexing agent is 30-50 g / L (for example, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L), the concentration of the reducing agent is 50-80 g / L (for example, 50 g / L, 60 g / L, 70 g / L or 80 g / L), and the pH of the assembly reaction solution is 9-11; more preferably, the mass volume ratio of the carbon nanohorn particles to the assembly reaction solution is 1:(20-30) g / mL (for example, 1:20 g / mL, 1:22 g / mL, 1:25 g / mL, 1:28 g / mL or 1:30 g / mL).

[0049] In an embodiment of the present invention, when assembling magnetic metal particles on the surface of carbon nanohorn particles, the pretreated carbon nanohorn particles are placed in an assembly solution containing metal salts, and the temperature is raised to 40-60° C. for stirring reaction. During the reaction, under the action of appropriate amounts of metal complexing agents and reducing agents in the assembly reaction solution, the metal salts can first be reduced to metal elements, and the metal elements are promoted to recombine with the carbon nanohorns, thereby forming carbon nanohorn@magnetic metal composite particles.

[0050] According to some preferred embodiments, in step (3), the mass ratio of carbon nanohorn@magnetic metal composite particles, organic carbon source and water is (50-250): (25-180): (300-500) (for example, it can be 50:25:300, 100:25:300, 250:25:300, 50:100:200, 50:180:300, 250:100:300 or 250:180:500); in step (3), when atomization drying is performed, the The injection rate of the mixed slurry is 10-25 mL / min (for example, it can be 10 mL / min, 12 mL / min, 15 mL / min, 18 mL / min, 20 mL / min or 25 mL / min), the inlet temperature of the atomizing dryer is 200-350°C (for example, it can be 200°C, 220°C, 250°C, 280°C, 300°C or 350°C), and the outlet temperature is 110-130°C (for example, it can be 110°C, 120°C or 130°C).

[0051] In the embodiment of the present invention, a certain amount of carbon nanohorn@magnetic metal composite particles and an organic carbon source are added to water and stirred to form a slurry, and the slurry is placed in an atomizing dryer for atomization drying. Under a certain temperature and air atmosphere, the water in the slurry evaporates and drives the carbon nanohorn@magnetic metal composite particles and the organic carbon source to diffuse uniformly around, thereby forming a composite hollow microsphere precursor. By rationally controlling the mass ratio of the organic carbon source, carbon nanohorn@magnetic metal composite particles and water in the slurry, it is not only conducive to the formation of the composite hollow microsphere precursor, but also enables the porous shaped carbon, carbon nanohorn and magnetic metal to fully exert the magnetic-dielectric-conductive synergistic effect, thereby maximizing the excellent wave absorption performance of the composite hollow microsphere.

[0052] At the same time, in the embodiment of the present invention, when atomizing and drying is performed, the size of the composite hollow microspheres can be reasonably controlled by reasonably controlling the slurry feeding speed, so that the obtained composite hollow microspheres have a larger micron-level macroscopic size, preventing the agglomeration of the composite hollow microsphere particles, and facilitating the use of the absorber.

[0053] According to some preferred embodiments, in step (4), the heat treatment temperature is 400-700°C (for example, 400°C, 500°C, 600°C or 700°C), and the time is 1-10h (for example, 1h, 2h, 5h, 8h or 10h).

[0054] In the embodiment of the present invention, the composite hollow microsphere precursor is heat-treated at the above temperature. On the one hand, the metal oxide that has not been completely reduced in the composite hollow microsphere precursor can be further reduced to a metal element. On the other hand, the organic carbon source can be fully carbonized into amorphous carbon, thereby enhancing the stability of the composite hollow microspheres, and further enhancing the application stability of the multi-element hierarchical composite hollow microspheres.

[0055] In summary, in the embodiment of the present invention, by using the carbon nanohorn coated with magnetic metal as the minimum unit and introducing a certain amount of amorphous carbon to form a composite hollow microsphere, on the one hand, the carbon nanohorn and the magnetic metal can form carbon nanohorn@magnetic metal composite particles, thereby enhancing the loss absorption performance of electromagnetic waves from the two aspects of dielectric loss and electromagnetic loss. On the other hand, amorphous carbon can be used as a defect to form a multi-heterogeneous interface with the carbon nanohorn and the magnetic metal, which can not only reduce the impact of high conductivity between conductive substances, but also enable the three to play a magnetic-dielectric-conductive synergistic effect, and further ensure the excellent wave absorption performance of the multi-composite hollow microsphere through multiple interface effects and multiple loss mechanisms. At the same time, the spherical shape gives the composite hollow microsphere high fluidity and high filling property, and has good processability when used as a wave absorber filler, which is conducive to the high volume fraction addition of the composite hollow microsphere, thereby reducing the density of the absorber and enhancing functionality.

[0056] The embodiment of the present invention also provides a use of the multi-element hierarchical composite hollow microsphere absorber described in any one of the above items in microwave absorption and catalytic degradation of wastewater.

[0057] The multi-component hierarchical composite hollow microspheres prepared in the embodiment of the present invention have good wave absorbing performance. When used as a wave absorbing agent, the volume ratio of the multi-component hierarchical composite hollow microspheres to paraffin in the absorber is preferably (30-90):1. The formed absorber can be applied to the field of military stealth, electromagnetic radiation protection of radio and television transmitters, microwave darkroom materials, building wave absorbing materials or electromagnetic shielding materials in radio communication equipment; at the same time, the multi-component hierarchical composite hollow microspheres can also be used for catalytic adsorption of wastewater.

[0058] In order to more clearly illustrate the technical solution and advantages of the present invention, a multi-element hierarchical composite hollow microsphere absorber and a preparation method thereof are described in detail below through several embodiments.

[0059] Embodiment 1:

[0060] (1) 10 g of carbon nanohorn particles were first placed in 60 mL of an acid solution (hydrochloric acid with a concentration of 0.6 mol) and stirred for 30 min, and then filtered to obtain acid-washed carbon nanohorn particles; then, the acid-washed carbon nanohorn particles were placed in 100 mL of an activated aqueous solution (the concentration of palladium ions was 0.10 mol / L), and stirred for reaction at 40° C. for 6 min, and then filtered, dried, and sieved to obtain pretreated carbon nanohorn particles;

[0061] (2) placing 10 g of the pretreated carbon nanohorn particles in 200 mL of an assembly reaction solution, stirring and reacting at 60° C. for 30 min, and filtering to obtain carbon nanohorn@magnetic metal composite particles; wherein the concentration of the metal salt (nickel sulfate) in the assembly reaction solution is 20 g / L, the concentration of the metal complexing agent (potassium sodium tartrate) is 50 g / L, the concentration of the reducing agent (sodium hypophosphite) is 50 g / L, and the pH of the assembly reaction solution is 10;

[0062] (3) 50 g of carbon nanohorn@magnetic metal composite particles were stirred and mixed with 150 g of organic carbon source (glucose) and 300 g of deionized water to obtain a mixed slurry, and the mixed slurry was atomized and dried using an air flow atomization dryer to obtain a composite hollow microsphere precursor; wherein the inlet temperature was 200° C., the outlet temperature was 120° C., and the injection speed was 20 mL / min;

[0063] (4) The composite hollow microsphere precursor was heat treated in a nitrogen-argon atmosphere, initially heated to 150°C, with a heating rate of 3°C / min, and kept warm for 20 min, then heated to 550°C, with a heating rate of 5°C / min, and kept warm for 4 h, to obtain a multi-element graded composite hollow microsphere absorber; wherein the density of the composite hollow microsphere is 2.0 g / cm 3 , the average diameter is 20 μm, and the thickness of the composite spherical shell is 10 μm.

[0064] Embodiment 2:

[0065] (1) 10 g of carbon nanohorn particles were first placed in 50 mL of an acid solution (hydrochloric acid with a concentration of 0.8 mol) and stirred for 30 min, and then filtered to obtain acid-washed carbon nanohorn particles; then, the acid-washed carbon nanohorn particles were placed in 80 mL of an activated aqueous solution (with a palladium ion concentration of 0.15 mol / L) and stirred at 40° C. for 6 min, and then filtered, dried, and sieved to obtain pretreated carbon nanohorn particles;

[0066] (2) placing 10 g of the pretreated carbon nanohorn particles in 250 mL of an assembly reaction solution, stirring and reacting at 60° C. for 30 min, and filtering to obtain carbon nanohorn@magnetic metal composite particles; wherein the concentration of the metal salt (nickel sulfate) in the assembly reaction solution is 20 g / L, the concentration of the metal complexing agent (potassium sodium tartrate) is 50 g / L, the concentration of the reducing agent (sodium hypophosphite) is 60 g / L, and the pH of the assembly reaction solution is 10;

[0067] (3) 100 g of carbon nanohorn@magnetic metal composite particles were stirred and mixed with 100 g of organic carbon source (glucose) and 500 g of deionized water to obtain a mixed slurry, and the mixed slurry was atomized and dried using an air flow atomization dryer to obtain a composite hollow microsphere precursor; wherein the inlet temperature was 200° C., the outlet temperature was 120° C., and the injection speed was 20 mL / min;

[0068] (4) The composite hollow microsphere precursor was heat treated in a nitrogen-argon atmosphere, initially heated to 150°C, with a heating rate of 3°C / min, and kept warm for 20 min, then heated to 550°C, with a heating rate of 5°C / min, and kept warm for 4 h, to obtain a multi-element graded composite hollow microsphere absorber; wherein the density of the composite hollow microsphere is 2.0 g / cm 3 , the average diameter is 50 μm, and the thickness of the composite spherical shell is 10 μm.

[0069] Embodiment 3:

[0070] (1) 10 g of carbon nanohorn particles were first placed in 30 mL of an acid solution (1 mol hydrochloric acid) and stirred for 60 min, and then filtered to obtain acid-washed carbon nanohorn particles; then, the acid-washed carbon nanohorn particles were placed in 50 mL of an activated aqueous solution (silver ion concentration was 0.15 mol / L), and stirred at 40° C. for 6 min, and then filtered, dried, and sieved to obtain pretreated carbon nanohorn particles;

[0071] (2) placing 10 g of the pretreated carbon nanohorn particles in 300 mL of an assembly reaction solution, stirring and reacting at 60° C. for 30 min, and filtering to obtain carbon nanohorn@magnetic metal composite particles; wherein the concentration of the metal salt (nickel sulfate) in the assembly reaction solution is 15 g / L, the concentration of the metal complexing agent (potassium sodium tartrate) is 45 g / L, the concentration of the reducing agent (sodium hypophosphite) is 60 g / L, and the pH of the assembly reaction solution is 10;

[0072] (3) 200 g of carbon nanohorn@magnetic metal composite particles were stirred and mixed with 100 g of organic carbon source (glucose) and 500 g of deionized water to obtain a mixed slurry, and the mixed slurry was atomized and dried using an air flow atomization dryer to obtain a composite hollow microsphere precursor; wherein the inlet temperature was 200° C., the outlet temperature was 120° C., and the injection speed was 20 mL / min;

[0073] (4) The composite hollow microsphere precursor was heat treated in a nitrogen-argon atmosphere, initially heated to 150°C, with a heating rate of 3°C / min, and kept warm for 20 min, then heated to 550°C, with a heating rate of 5°C / min, and kept warm for 4 h, to obtain a multi-element graded composite hollow microsphere absorber; wherein the density of the composite hollow microsphere is 3.0 g / cm 3 , the average diameter is 50 μm, and the thickness of the composite spherical shell is 20 μm.

[0074] Embodiment 4:

[0075] Example 4 is substantially the same as Example 1, except that in step (3), the mass ratio of carbon nanohorn@magnetic metal composite particles, organic carbon source (glucose) and deionized water is 30:30:300.

[0076] Embodiment 5:

[0077] Example 5 is substantially the same as Example 1, except that in step (3), the mass ratio of carbon nanohorn@magnetic metal composite particles, organic carbon source (glucose) and deionized water is 50:20:300.

[0078] Embodiment 6:

[0079] Example 6 is basically the same as Example 1, except that in step (3), the injection rate of the mixed slurry is 30 mL / min, the inlet temperature of the atomizing dryer is 180° C., and the outlet temperature is 100° C.

[0080] Comparative Example 1

[0081] (1) 2400 mL of anhydrous ethanol and 600 mL of deionized water were mixed uniformly, and 15 g of resorcinol, 62.5 g of formaldehyde solution (37 wt.%), and 100 g of concentrated ammonia water (25 wt.%) were added to the mixture. After stirring and mixing uniformly, 3 g of ferrosoferric oxide nanoparticles (particle size 50 nm) were added, and the mixture was stirred and reacted at 40° C. for 12 h to obtain phenolic resin-coated nanoparticles.

[0082] (2) 8 g of soluble starch and 2 g of sucrose are added to 20 g of water and stirred thoroughly to dissolve; the above-mentioned phenolic resin-coated nanoparticles are then added under stirring to obtain a spray slurry; the prepared slurry is subjected to atomization drying treatment using an air flow atomization drying device with an inlet temperature of 220° C., an outlet temperature of 120° C., and a drying atmosphere of air to obtain a spherical precursor.

[0083] (3) The obtained precursor is then heat treated at 750° C. for 3 h in a hydrogen / argon (hydrogen content 5%) mixed gas atmosphere to obtain a magnetic metal-carbon composite microsphere absorber with a hollow structure; wherein the molar ratio of carbon to metal in the hollow microsphere absorber is 8:1, and the density is 0.93 g / cm 3 , spherical shell thickness is 950nm and average particle size is 17μm.

[0084] The composite hollow microsphere absorbers prepared in Examples 1 to 6 and Comparative Example 1 were subjected to performance tests. The test results are shown in Table 1.

[0085] Table 1

[0086]

[0087]

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A multi-element hierarchical composite hollow microsphere absorber, characterized in that: The multi-element hierarchical composite hollow microspheres are composed of a hollow core and a composite spherical shell; wherein the hollow core is an air cavity, and the composite spherical shell is composed of porous amorphous carbon as a continuous phase and carbon nanohorn@magnetic metal composite particles as a dispersed phase.

2. The composite hollow microsphere absorber according to claim 1, characterized in that: The density of the multi-element graded composite hollow microspheres is 0.5-3.0 g / cm 3 , diameter is 5-100μm, and the thickness of the composite spherical shell is 0.1-20μm.

3. The composite hollow microsphere absorber according to claim 1, characterized in that: The porous amorphous carbon is obtained by carbonizing a water-soluble organic carbon source; wherein the organic carbon source is at least one of glucose, fructose, sucrose, citric acid or dopamine; The magnetic metal is at least one of metallic iron, metallic cobalt or metallic nickel.

4. A method for preparing a multi-element hierarchical composite hollow microsphere absorber according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) pretreating the carbon nanohorn particles to obtain pretreated carbon nanohorn particles; (2) placing the pretreated carbon nanohorn particles in an assembly reaction solution to self-assemble with a magnetic metal to obtain carbon nanohorn@magnetic metal composite particles; (3) mixing the carbon nanohorn@magnetic metal composite particles with an organic carbon source and water, and then atomizing and drying the mixed slurry using an atomizing dryer to obtain a composite hollow microsphere precursor; (4) heat-treating the composite hollow microsphere precursor to obtain the multi-element graded composite hollow microsphere absorber.

5. The preparation method according to claim 4, characterized in that: In step (1), the pretreatment comprises the steps of sequentially performing acid washing and activation treatment on the carbon nanohorns; During the pickling process, the mass volume ratio of the carbon nanohorn particles to the acid solution is 1:(2-6) g / mL, and the acid solution is at least one of acetic acid, hydrochloric acid, sulfuric acid or nitric acid; Preferably, the concentration of the acid solution is 0.5-1.0 mol / L, and the pickling time is 30-120 min.

6. The preparation method according to claim 4, characterized in that: In step (1), during the activation treatment, the mass volume ratio of the carbon nanohorn particles to the activated aqueous solution is 1:(5-10) g / mL, and the solute in the activated aqueous solution is at least one of tin ions, palladium ions, silver ions, gold ions or platinum ions; Preferably, the concentration of the activated aqueous solution is 0.05-0.15 mol / L, and the activation treatment time is 5-10 min.

7. The preparation method according to claim 4, characterized in that: In step (2), the assembly reaction solution comprises a metal salt, a metal complexing agent, a reducing agent and a pH adjusting agent; wherein the metal salt is at least one of an iron salt, a nickel salt or a cobalt salt, the metal complexing agent is at least one of ammonium sulfate, potassium sodium tartrate or ethylenediaminetetraacetic acid, the reducing agent is at least one of sodium hypophosphite, hydrazine hydrate, formaldehyde or sodium borohydride, and the pH adjusting agent is at least one of sodium hydroxide or potassium hydroxide; Preferably, in the assembly reaction solution, the concentration of the metal salt is 10-20 g / L, the concentration of the metal complexing agent is 30-50 g / L, the concentration of the reducing agent is 50-80 g / L, and the pH of the assembly reaction solution is 9-11; More preferably, the mass volume ratio of the carbon nanohorn particles to the assembly reaction solution is 1: (20-30) g / mL.

8. The preparation method according to claim 4, characterized in that: In step (3), the mass ratio of carbon nanohorn@magnetic metal composite particles, organic carbon source and water is (50-250): (25-180): (300-500); In step (3), when atomization drying is performed, the injection speed of the mixed slurry is 10-25 mL / min, the inlet temperature of the atomization dryer is 200-350° C., and the outlet temperature is 110-130° C.

9. The preparation method according to claim 4, characterized in that: In step (4), the heat treatment temperature is 400-700°C and the time is 1-10h.

10. Use of the multi-element hierarchical composite hollow microsphere absorber according to any one of claims 1 to 3 or the multi-element hierarchical composite hollow microsphere absorber prepared by the preparation method according to any one of claims 4 to 9 in microwave absorption and catalytic degradation of wastewater.

Citation Information

Cited By

  • Preparation method of biochar wave-absorbing material with non-uniform pore structure

    CN120774411A

  • Preparation method of non-uniform pore structure biochar wave absorbing material

    CN120774411B